PENGARUH PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM TERHADAP BELANJA LANGSUNG - Octaviani, Nanda Eka; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to find out whether the Local Own Source Revenue and General Allocation Fund haspositive influence to the direct expenditure of local government of East Java Province in 2013-2015 periods. Thisresearch has been carried out by using secondary data in the form of statement of budgetary realization of thelocal government which has been obtained from Statistics Indonesia (BPS) and The Audit Board of the Republicof Indonesia (BPK RI). The data analysis has been done by using multiple linear regressions analysis with thesupport of the SPSS (Statistical Product and Service Solutions) application. The result of coefficient test showsthat 96.2% variation or the change of direct expenditure can be explained by the variation of independentvariable of Local Owned Source Revenue and General Allocation Fund, meanwhile the remaining 3.8% has beenexplained by other variables which are not included in the research model. The result of the research shows thatLocal Owned Source Revenue and General Allocation Fund has positive influence to the direct expenditure. Thelevel of dependency of direct expenditure of the local government in East Java Province is more dominant to theLocal Owned Source Revenue and General Allocation Fund.Keywords: Local owned source revenue, general allocation fund, direct expenditure.